2021
DOI: 10.3390/molecules27010098
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Plastic Waste: Removal of Colorants from HDPE Using Biosolvents

Abstract: Plastics recycling remains a challenge due to the relatively low quality of the recycled material, since most of the developed recycling processes cannot deal with the additives present in the plastic matrix, so the recycled products end up in lower-grade applications. The application of volatile organic solvents for additives removal is the preferred choice. In this study, pretreatment of plastic packaging waste to remove additives using biosolvents was investigated. The plastic waste used was high-density po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Dissolution generates quality recyclate at high yields and reasonable prices but has high environmental impacts due to organic solvent use. Switching to biobased solvents such as limonene could minimize fossil resource consumption, but analyses must be conducted on their economic and environmental effects . Switchable solvents, which have reversibly changeable physical properties, offer an opportunity to recycle laminated or multipolymer products. , Ideally, the selected solvent should dissolve the polymer at low temperatures to minimize heat requirements and have a low boiling point to enable energy-efficient recovery by distillation as well as sufficient removal during drying to produce food-grade quality polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Dissolution generates quality recyclate at high yields and reasonable prices but has high environmental impacts due to organic solvent use. Switching to biobased solvents such as limonene could minimize fossil resource consumption, but analyses must be conducted on their economic and environmental effects . Switchable solvents, which have reversibly changeable physical properties, offer an opportunity to recycle laminated or multipolymer products. , Ideally, the selected solvent should dissolve the polymer at low temperatures to minimize heat requirements and have a low boiling point to enable energy-efficient recovery by distillation as well as sufficient removal during drying to produce food-grade quality polymer.…”
Section: Resultsmentioning
confidence: 99%
“…Although it has already been reported that HDPE is soluble in toluene, [27][28][29][32][33][34] xylene, 33,34,57,58 and D-limonene 39 at 110 °C, no dissolution is predicted by the COSMO-SAC model. At this temperature, the experimental solubility limit has only been reported in toluene being between 14.56 wt% 28,35 and 23.1 wt%.…”
Section: Thermodynamic Estimations: Solvent Screening Using Cosmo-sacmentioning
confidence: 91%
“…31 HDPE, the focus of the present study, was the subject of various physical recycling studies using dissolution and precipitation, mostly using toluene, 27,29,[32][33][34][35] xylene 26,33,34 or petroleum ether-based solvents. [36][37][38] Only in 2022, Ferreira et al 39 proposed the use of D-limonene, a biobased solvent, for the dissolution of HDPE. However, the objective of that work was the recovery of dyes from the plastic, and plastic recovery itself was not considered in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is uncertain whether the various additives have negative impacts on the process of microbial biodegradation due to their levels of toxicity. Therefore, it is recommended that further studies eliminate additives and other contaminants using pretreatment processes, such as extraction, prior to investigating biodegradation ( Ferreira et al, 2022 ). Alternatively, the integration of strains with specific degradation additives into synthetic consortia could be effective in both degrading the various additives and resolving PE polymers in synergy with other functional bacteria in the consortia.…”
Section: Future Perspectives Toward Pe Biodegradation and Valorizationmentioning
confidence: 99%